2014
DOI: 10.1111/luts.12050
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Involving Beta‐3 Adrenergic Receptors Modulate Cold Stress‐Induced Detrusor Overactivity in Conscious Rats

Abstract: A high dose of the beta-3 agonist CL316243 could modulate cold stress-induced detrusor overactivity. Therefore, one of the mechanisms in cold stress-induced detrusor overactivity includes a pathway involving beta-3 ARs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Our previous study showed that the cold stress-induced bladder overactivity of Sprague-Dawley (SD) rats without any underlying disease was inhibited by treatments with 1.0 mg/kg CL316243, another β 3adrenergic receptor agonist. 19 Thus, we concluded that the cold stress-induced bladder overactivity in normal SD rats is mediated with pathways involving β 3 -adrenergic receptors. However, in the present study, the bladder overactivity of GK rats was not inhibited by treatments with either 0.1 mg/kg or 1.0 mg/kg mirabegron, even though expression of β 3 -adrenergic receptor mRNA and protein were detected within the urinary bladders.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our previous study showed that the cold stress-induced bladder overactivity of Sprague-Dawley (SD) rats without any underlying disease was inhibited by treatments with 1.0 mg/kg CL316243, another β 3adrenergic receptor agonist. 19 Thus, we concluded that the cold stress-induced bladder overactivity in normal SD rats is mediated with pathways involving β 3 -adrenergic receptors. However, in the present study, the bladder overactivity of GK rats was not inhibited by treatments with either 0.1 mg/kg or 1.0 mg/kg mirabegron, even though expression of β 3 -adrenergic receptor mRNA and protein were detected within the urinary bladders.…”
Section: Discussionmentioning
confidence: 77%
“…Our previous study showed that the cold stress‐induced bladder overactivity of Sprague–Dawley (SD) rats without any underlying disease was inhibited by treatments with 1.0 mg/kg CL316243, another β 3 ‐adrenergic receptor agonist 19 . Thus, we concluded that the cold stress‐induced bladder overactivity in normal SD rats is mediated with pathways involving β 3 ‐adrenergic receptors.…”
Section: Discussionmentioning
confidence: 88%
“…We previously showed that the same low dose (0.1 mg/kg) of the β 3 ‐AR agonist CL316243 did not inhibit the cold stress‐induced responses in SD rats . However, a higher dose, 1.0 mg/kg, did inhibit the cold stress‐induced detrusor overactivity . Thus, we suggested that while the pathways involving β 3 ‐ARs could mediate the cold stress‐induced responses, the effects were dose dependent.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, treatment of the SHRs with mirabegron alone did not inhibit the cold stress‐induced detrusor overactivity patterns. We previously showed that the same low dose (0.1 mg/kg) of the β 3 ‐AR agonist CL316243 did not inhibit the cold stress‐induced responses in SD rats . However, a higher dose, 1.0 mg/kg, did inhibit the cold stress‐induced detrusor overactivity .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation